Material Agency
XX, 256 p. 49 illus.
Keywords: Agency is a key theme that cross-cuts a wide raft of disciplines in the humanities, social sciences and beyond; yet it is invariably discussed separately behind closed disciplinary doors. Within archaeology, agency has been characterized as a uniquely human attribute, and a means of incorporating individual intentionality into theoretical discourse. In other domains, however, notions of non-human and ‘material’ agency have been finding currency, and it is our aim to introduce some of these themes into archaeology and develop a non-anthropocentric approach to agency. It is anticipated that such a perspective will not only help us achieve more convincing interpretations of the past, giving a more active role to material culture, but also throw new light on the changing role of artifacts in the present and the future. This book is a groundbreaking attempt to address questions of non-human and material agency from a wide range of perspectives and disciplines: archaeology, anthropology, sociology, cognitive science, philosophy, and economics. The editors and authors demostrate that a distributed, relational approach to agency, incorporating both humans and artifacts, has important ramifications for how we understand material culture.